Analisis Penggunaan Microsoft Teams dalam Pembelajaran Daring di SD Muhammadiyah 26 Surabaya - Sulistiani, Sulistiani; Putra, Deni Adi; Pribowo, Fitroh Setyo Putro (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The research objective is to analyze the micro team users in courageous learning, with the research it is hoped that educational institutions can access the Microsoft teams application to implement learning environments at the elementary to tertiary level. This research uses descriptive qualitative research. This research uses qualitative analysis methods with semistructured interview techniques. Based on the results of the questionnaire from the aspects of attention, appreciation and duration of positive responses to the use of the Microsoft team in learning at SD Muhammadiyah 26 Surabaya, while the results of interviews with 2 informants can show that learning using Microsoft Teams is a safe platform to support and facilitate educators and students alike. Virtual via Microsoft Teams. Researchers have suggestions for further learning or for teachers or for schools, namely that educators can use the Microsoft teams in courage-based learning activities, schools need to maximize the use of the Microsoft teams during bold learning so that learning is effective.